Analysis of a Physical Education Service-Learning proposal aimed at underage with adverse childhood experiences - Beatriz Garay Ibáñez de Elejalde; Elena López-de-Arana Prado; María Teresa Vizcarra Morales; Xabier Larrazabal Barrio (Contextos educativos, 2021)
It is analyzed a service-learning experience (SL) that encourages physical activity in young people who manifest socio-emotional and behavioral difficulties. This situation may be an evidence of early adverse experiences. This is usually indicative of having had adverse childhood experiences. Many of these underage end up enrolled in the Educational Therapeutic Unit (UTE) or in the Child Psychiatry Unit (UPI). The Faculty of Education and Sports of the University of the Basque Country (UPV/EHU) offered the possibility of carrying out the Final Degree Projects (FDP) through SL experiences in Physical Education that were aimed at young people attended in hospital setting. The objective of this ethnographic study is to describe what this experience generated in the beneficiary group, in the 14 young people attended; to know the valuation of the entities; and to identify the learning of the university student-tutor who completed the FDP. The content of the auto-ethnographic journal written by the university student-tutor, and the interview with the clinical team and the special education teachers were analyzed. The results lead to the conclusion that the experience of SL in Physical Education helped to break the apathy and inactivity shown by the beneficiary group, and that to the student-university tutor it was useful in the development of his professional skills.